Development of characteristic value for compressive strength properties of selected Malaysian tropical hardwood timber / Anis Azmi - Azmi, Anis (2019)
Timber is one of the renewable and recyclable natural resource and commonly used in structural, outdoor, indoor equipment and furniture industry. It is not only a renewable and recyclable resource but also energy-efficient compared to other materials such as steel and concrete in term of material production, thus making it as a lowest embodied energy material. Essentially, timber plays an important role that acts as carbon sink in order to reduce carbon emission. In construction industry, timber often is used as trusses, beams, joists and many others. Usage of timber as structural material is not new, in fact it was used over centuries ago. As time passes, developments in timber engineering are expanding rapidly with various types of new innovation timber components as a structural material that enabling timber to compete with other engineering material in building forms.